BIOGENIC GAS(?) IN FLUID INCLUSIONS FROM SANDSTONES IN CONTACT WITH OIL-MATURE COALS - Ohm S.E.; Karlsen D.A. (My University, 2007)
This study was initiated to investigate if coals on the Norwegian offshore continental shelf (NOCS) expel petroleum and in which form. The results revealed that equally isotopically light methane (C1) was released from fluid inclusions in sandstones and from adjacent coal (-60.9 to -72.7‰). The analyzed samples were collected from cored northern North Sea and mid-Norwegian shelf wells in the depth interval 3924-5095 m (12,874-16,716 ft). The vitrinite reflectance (Ro) values of the coals range between 0.53 and 1.12 %, with most values between 0.8 and 1.0%. Only minor C2+ fractions were released showing much heavier gas isotope signatures similar to values seen in our in-house NOCS gas isotope database for comparable depths. The similar light C1 isotope values released both from the coals and from the fluid inclusions in the adjacent sandstones suggest that the origin of the gas is the coal, and that no isotope fractionation occurs during release of the gas in nature. Traditional isotope interpretation schemes suggest the C1 to have a biogenic origin, whereas recently published data also show the possibility for an early mature thermogenic origin. The isotope values represent averages of the total gas released from all the individual disintegrated fluid inclusions in each sample. These did not form simultaneously, but during multiple events potentially covering several million years. The release of isotopically light C1 proves gas presence in the sandstone at the time of fluid-inclusion formation. We therefore speculate that significant volumes of isotopically light C1 have been expelled from the analyzed coals over time. The expelled isotopically light C1 may mix with mature thermogenically produced gas and skew the overall methane isotope values of gas accumulations toward lighter values, thus explaining the isotopically lighter-than-expected gas accumulations on the NOCS (e.g., Troll, Frigg, and Draugen fields). Copyright © 2007. The American Association of Petroleum Geologists. All rights reserved.